CHARACTERISTICS OF STRATEGIC PLANNING AND ITS RELATIONSHIP TO INCREASING PERFORMANCE IN SOCIAL INSTITUTIONS OF THE SHARJAH GOVERNMENT - Alkaabi , Obaid; Alomosh, Ahmad (Al-Adab Journal, 2025)
This research explores the characteristics of strategic planning and its impact on increasing performance in social institutions in the Government of Sharjah, focusing on two pivotal case studies: the Department of Social Services and the Sharjah Social Security Fund; The results show that systematic and integrated strategic planning contributes significantly to improving social services and increasing performance by setting clear goals and developing effective strategies to address diverse social challenges. The case studies highlight how the Department of Social Services and the Sharjah Social Security Fund used strategic planning models to enhance social security and support vulnerable groups in a targeted and impactful manner. By applying models such as SWOT and PESTEL, and leveraging management information systems to measure performance, these two institutions have been able to achieve tangible social impact and improve the quality of life for beneficiaries; The research shows the importance of actual responses from citizens as indicators of success and their role in improving and modifying programs and services, which enhances the positive impact of social enterprises in society. In addition, the results highlight the importance of innovation and cooperation with various partners to expand the scope of services and enhance overall performance, which emphasizes the vital role of strategic planning in achieving sustainable and comprehensive social development